Systemic manifestation of necrotic erythema nodosum leprosum: A case report of a fatal leprosy - Maulida, Mimi; Vella, Vella; Budini, Sulamsih S.; Kamarlis, Reno K.; Junaidi, Fachrul; Pradistha, Aldilla; Bulqiah, Mikyal (Narra Sains Indonesia, 2023)
Necrotic erythema nodosum leprosum (ENL) is an uncommon manifestation of type 2 lepra reaction, encountered in lepromatous and borderline lepromatous cases of leprosy. Necrotic ENL is associated with the involvement of multiple organs, therefore delayed diagnosis and treatment will lead to complications and poor prognosis. The aim of this case report was to report a challenging case of necrotic ENL misdiagnosed with multiple cellulitis since there were no signs of prior leprosy nor had any antimycobacterial treatment. A 45-year-old man was presented to the surgery department of Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia, with complaints of fever, joint pain, and painful tender skin lesions with ulceration over the trunk, extremities, and ears for one month. The patient was diagnosed clinically with multiple cellulitis and underwent a debridement procedure. Clinical improvement was absent, the patient was then consulted to the dermatology department. Physical examination showed normal vital signs, madarosis, inguinal lymphadenopathy, thickening of nerves, and sensation of numbness in both hands and feet. Laboratory examinations on admission showed leucocytosis, anemia, thrombocytopenia, hypoalbuminemia, hypocalcemia, and elevated creatinine and ureum level. A slit skin smears examination yielded positive acid-fast bacilli (AFB) with a bacteriological index (BI) value of 3+ and morphological index (MI) of 72%. The patient was diagnosed with lepromatous leprosywith necrotic ENL reaction. Intravenous methylprednisolone and cefoperazone-sulbactam were given. Multidrug therapy mulitbacillary (MDT-MB) without dapsone, and ofloxacin 400 mg was initiated. On day 17, the patient had septic shock. The patient became unconscious and experienced death. This case highlights that medical professionals should be aware of the various manifestations of necrotic ENL to correctly diagnose and provide treatment as soon as possible to prevent mortality, especially in leprosy-endemic country, Indonesia.